Analisis Fitokimia dan Uji Aktivitas Antioksidan Ekstrak Etanol Kulit Batang Alpukat Mentega (Persea Americana Mill) - Chusnah, Hudallil; Hafshah, Mutista (Universitas Negeri Gorontalo, 2025)
Lack of physical activity, fast food products, and increased stress due to work pressures are all dangers that might induce unnoticed changes in the body that can lead to degenerative diseases. The existence of free radicals, which can cause cancer and damage cells in the body, might trigger the emergence of degenerative disorders. Antioxidants can help to prevent degenerative disorders caused by the presence of free radicals. The purpose of this study is to investigate the yield percentage, secondary metabolite chemicals, and the IC50 value of the antioxidant activity of butter avocado stem bark (Persea americana Mill). The maceration method is used in the extraction of avocado butter bark. The obtained extraction results give as much as. Flavonoids, tannins, saponins, and alkaloids are among the secondary metabolites found in butter avocado stem bark. The antioxidant activity was then determined using the DPPH (2,2-diphenyl-1-picryhidrazil) technique. The ethanol extract of avocado butter stem bark exhibited an IC50 value of 137.81 ppm, indicating that it was a natural product with moderate antioxidant activity that may be exploited as a natural antioxidant source.